The design and performance of a low-lift wind-pump for irrigation purposes in the rural areas. - Ahmad, Desa (1982)
An attempt at harnessing windpower for pumping water in rural areas is described. The work carried out involved the design of a low cost, low-lift wind-pump driven by horizontal axis wind-mill the detailed design of which is given in a separate report. The reduction in cost was suggested by adopting a substantially cheaper methods of construction based on locally available material. Pump was designed using the principle of centrifugal force based on data from Tanzania and IRRI reports. The estimated pumping requirement was 50 m3/day utilising windpower within a speed range of 3 to 7m/s on 1 to 2 hectares of land grown with dry crops.